ESAT-6-Ag85C-polyHistag Antigen Fusion is Potential as Vaccine Candidate for Tuberculosis - Ratu Purwanti; Agnes Rengga Indrati; Nida Suraya; Maya Marinda Montain; Ines Atmosukarto; Neni Nurainy; Ida Parwati (The Indonesian Biomedical Journal, 2023)
BACKGROUND: BCG vaccine has been proven to be effective protection against tuberculosis (TB) meningitis and miliary TB. However, for protection against pulmonary TB, the results remains vary widely. Recombinant vaccine consisting of two immunodominant Mtb antigens ESAT-6-Ag85C-polyHistag (EAH) is currently being developed as a new TB vaccine candidate for booster. An immugonecity test for vaccine candidates is required in the initial phase to evaluate cellular immune response. This study was conducted to evaluate the cellular immune response by measuring interferon-gamma (IFN-γ) cytokines produced by T cells after ex vivo stimulation by TB EAH antigen fusion.METHODS: Peripheral blood mononuclear cells supernatant samples were collected from 16 new pulmonary TB subjects, 17 pulmonary TB in treatment subjects, and 10 healthy subjects. Samples were tested for IFN-γ level with enzyme-linked immunosorbent assay (ELISA). Kruskal-Wallis test was used to test the differences between IFN-γ levels among three groups, and followed by post-hoc analysis using Mann Whitney.RESULTS: The median of IFN-γ levels for new pulmonary TB, pulmonary TB in treatment, and healthy subjects were 17.09 (2.65-140.14) pg/mL, 4.36 (2.43-21.41) pg/mL, and 2.91 (2.39-3.85) pg/mL, respectively. There were significant differences of IFN-γ levels between new pulmonary TB group and pulmonary TB in treatment group (p=0.012), between new pulmonary TB group and healthy group (p=0.001), and also between pulmonary TB in treatment group and healthy group (p=0.035).CONCLUSION: Results show that TB EAH could stimulate cell-mediated immune responses in the three groups, with the highest IFN-γ levels are found in new pulmonary TB group, suggesting a potential immunodominant antigen fusion for vaccine candidate development.KEYWORDS: Ag85C, ESAT-6, immunogenicity test, IFN-γ, TB vaccine candidate, tuberculosis